Teaching Wellness in a College Physical Education Course: Pre/Post Outcomes over the Semester - Lothes II, John (Building Healthy Academic Communities Journal, 2020)
Background: Over the years, college student wellness has become an issue of concern. This study reports the results that physical education classes and effects they on college student overall wellness over the course of a semester. Aim: This study examines the pre/post outcomes of a physical education course on 12 dimensions of wellness from the start of the semester to the end of the semester. Methods: College students (N = 1,497) taking a PED101 were assessed at the beginning (pre) and end (post) of the semester for wellbeing outcomes according to the Wellness Inventory. Quantitative outcomes from the Wellness Inventory were compared pre/post as well as demographic variables (e.g., gender and health status). Results: All 12 dimensions of wellness showed increases from the start of the semester to the end of the semester. The results found statistically significant changes between the pre and post assessments for all dimensions of wellness outcomes. There were also significant changes between the pre and post assessments when investigating differences based on sex and health status. Conclusion: PED101 courses can be useful interventions to help move college students towards wellness.